2011
DOI: 10.1016/j.molcel.2011.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Silent Chromatin through Replication Requires SWI/SNF-like Chromatin Remodeler SMARCAD1

Abstract: Epigenetic marks such as posttranslational histone modifications specify the functional states of underlying DNA sequences, though how they are maintained after their disruption during DNA replication remains a critical question. We identify the mammalian SWI/SNF-like protein SMARCAD1 as a key factor required for the re-establishment of repressive chromatin. The ATPase activity of SMARCAD1 is necessary for global deacetylation of histones H3/H4. In this way, SMARCAD1 promotes methylation of H3K9, the establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
222
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(241 citation statements)
references
References 69 publications
15
222
0
1
Order By: Relevance
“…9,[16][17][18][19] Depletion of the WICH complex, comprising SNF2h and the Williams Syndrome Transcription Factor WSTF, is accompanied by an increase in heterochromatin marks following S phase. 17 WICH seems to be responsible for keeping chromatin accessible after its assembly.…”
Section: Keeping Chromatin Quietmentioning
confidence: 99%
See 2 more Smart Citations
“…9,[16][17][18][19] Depletion of the WICH complex, comprising SNF2h and the Williams Syndrome Transcription Factor WSTF, is accompanied by an increase in heterochromatin marks following S phase. 17 WICH seems to be responsible for keeping chromatin accessible after its assembly.…”
Section: Keeping Chromatin Quietmentioning
confidence: 99%
“…9,10 Heterochromatin promotes genome stability by repressing transcription and illegitimate recombination between repetitive DNA elements. 20,21 In particular, heterochromatic repeats flanking centromeres are important for centromere function, mediating proper chromosome segregation.…”
Section: Maintaining Silence Through Remodeling: a New Playermentioning
confidence: 99%
See 1 more Smart Citation
“…2 Nine pedigrees with Basan syndrome have been reported worldwide. [3][4][5][6][7][8][9][10] Recently, Marks et al 10 identified SMARCAD1 (OMIM 612761) as a promising candidate gene for Basan syndrome in an American family. This gene encodes a member of the SNF subfamily of helicase proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This gene encodes a member of the SNF subfamily of helicase proteins. 9 Variants in the SMARCAD1 gene were previously reported in patients with adermatoglyphia (ADG, OMIM 136000), which is characterized by the congenital absence of epidermal ridges. 11,12 To date, five variants (c.378+1G4T, c.378+1G4A, c.378+2T4C, c.378+3A4T and c.378 +5G4C) have been reported in patients with ADG and Basan syndrome.…”
Section: Introductionmentioning
confidence: 99%